CD31 (JC70) expression in plasma cells: an immunohistochemical analysis of reactive and neoplastic plasma cells. Issue 6 (June 1997) - Govender, D; Harilal, P; Dada, M; Chetty, R
Abstract : AIMS: To investigate the immunohistochemical expression of CD31 (JC70) in normal and neoplastic plasma cells. METHODS: Plasma cells in bone marrow biopsies and extramedullary locations were examined. All extramedullary biopsies were formalin fixed and paraffin embedded. The bone marrow biopsies were fixed in formal acetic acid and embedded in paraffin wax. Twenty multiple myelomas (12 bone marrow and eight extramedullary deposits), 10 extramedullary plasmacytomas, and 30 biopsies with reactive plasma cells (10 bone marrow, 20 extramedullary biopsies) were stained with anti-CD31 (JC70) using the streptavidin-biotin detection system with diaminobenzidine as a chromogen. Antigen retrieval in bone marrow biopsies was achieved by pressure cooking. In all other biopsies, antigen retrieval was achieved by microwave pretreatment. RESULTS: All 20 extramedullary cases with reactive plasma cells showed intense membrane staining. Focal staining was detected in reactive plasma cells in bone marrow biopsies. Five of 10 plasmacytomas showed membrane staining. None of the cases of multiple myeloma, either medullary or extramedullary, showed any immunoreactivity for CD31. CONCLUSIONS: CD31, a member of the immunoglobulin supergene family of cell adhesion molecules, is strongly expressed in extramedullary reactive plasma cells, focally in bone marrow reactive plasma cells, and occasionally in extramedullary plasmacytomas.